The Reasons of Code Switching Found in Pamungkas' Speech During Podcast Talks/Interviews - I Gusti Ngurah Deni Irawan; Made Iwan Indrawan Jendra; I Wayan Juniartha (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study concerned with the code switching phenomenon involving Indonesian-English found in Pamungkas’ speech during podcast talks or interviews. The study aims to analyze the reasons and classify the most and least type of the code switching by Pamungkas as the interviewees in the four podcast episodes on Spotify. Quantitative and qualitative method were used in this study. The data were analyzed according to theory proposed by Hoffman (1991) about seven reasons of code switching. The result of this study showed there are 78 code switching and all reasons from the theory were found. Based on the finding, expressing group identity was the dominant reason with 28 (35,89%) data, followed by 22 (28,21%) data of talking about particular topic, 11 (14,11%) data of interjection, 7 (8,97%) data of being emphatic about something, 6 (7,70%) data of repetition used for clarification, and 3 (3,84%) data of quoting somebody else. Meanwhile, intention of clarifying the speech content for interlocutor was only represented by 1 (1,28%) data, found in those four podcast episodes uttered by Pamungkas as the interviewees.